The Burden and Risk Factors Associated with Infectious Diseases among Refugees in a Camp for Migrants in Porto Alegre: A Cross-Sectional Survey - Mauricio Da Silva Roxkow Fraga; Filipe Andre Angst; James January; Agnes Madziwa; Laston Gonah; Alexandre Lazzarotto (Ubiquity Press, 2024)
Refugees usually face a disproportionate burden of infectious diseases. Recently, Brazil has experienced an influx of refugees which demands the need for scaling up public health efforts to address the challenges. The research sought to study the burden and risk factors associated with infectious diseases among refugees received in the city of Porto Alegre. This was a cross-sectional study of 261 newly arrived refugees. The study sample was predominantly composed of Venezuelans (50.6%) and Haitians (44%), male (146: 56.7%), single (30.7%), with an average age of 33.38 (± 7.30) years. The average schooling was 10.42 (± 2.09) years. Diseases with the highest prevalence were influenza, whooping cough, diphtheria, and tuberculosis. There was significant association between the country of origin and presence of symptoms for infectious and contagious diseases, which warrants targeted interventions for reducing the incidence of these diseases among refugees in Brazil.